ERACS in National Health Insurance: Clinical Benefits and Economic Challenges: JEL Classification: I11, I13, I18, H51, D61 - Ageng Sunjoyo; Imronudin Imronudin; Muzakar Isa (Newinera Publisher, 2026)
Enhanced Recovery After Cesarean Section is a perioperative care pathway designed to improve maternal recovery and optimize healthcare resource utilization; however, its implementation within Indonesia’s National Health Insurance system remains constrained by fixed reimbursement mechanisms. This systematic review aimed to evaluate the clinical and economic outcomes of Enhanced Recovery After Cesarean Section in the context of national health insurance and to assess its policy implications. A systematic review was conducted of 27 studies involving more than 9,000 cesarean deliveries, with analysis focusing on length of hospital stay, hospitalization costs, pain control, postoperative complications, opioid use, and patient satisfaction. The findings demonstrate that Enhanced Recovery After Cesarean Section consistently shortens hospital stay, improves postoperative pain control, reduces opioid consumption and complication rates, and enhances maternal satisfaction without increasing readmissions. Several studies also reported reductions in direct hospital costs, primarily driven by decreased length of stay. Despite these benefits, the fixed case-based reimbursement system limits financial incentives for hospitals, creating a mismatch between clinical efficiency and economic returns. In conclusion, Enhanced Recovery After Cesarean Section provides significant clinical and economic advantages but requires reimbursement reform and policy alignment to enable sustainable implementation within Indonesia’s universal health coverage system.